Disintermediation and the role of banks in Europe: An international comparison - Reinhard H. Schmidt; Andreas Hackethal; Marcel Tyrell (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 1998)
The paper presents an empirical analysis of the alledged transformation of the financial systems in the three major European economies, France, Germany and the UK. Based on a unified data set developed on the basis of national accounts statistics, and employing a new and consistent method of measurement, the following questions are addressed: Is there a common pattern of structural change; do banks lose importance in the process of change; and are the three financial systems becoming more similar? We find that there is neither a general trend towards disintermediation, nor towards a transformation from bank-based to capital market-based financial systems, nor for a loss of importance of banks. Only in the case of France strong signs of transformation as well as signs of a general decline in the role of banks could be found. Thus the three financial systems also do not seem to become more similar. However, there is also a common pattern of change: the intermediation chains are lengthening in all three countries. Nonbank financial intermediaries are taking over a more important role as mobilizers of capital from the non-financial sectors. In combination with the trend towards securitization of bank liabilites, this change increases the funding costs of banks and may put banks under pressure. In the case of France, this change is so pronounced that it might even threaten the stability of the financial system.
urn:nbn:de:hebis:30-18169
Keywords: G1; G2; 330; (dis-)intermediation; bank-based financial systems; capital market-based financial systems; Finanzsektor; Finanzsystem; Verbriefung; Finanzintermediation; Vergleich; Frankreich; Deutschland; Großbritannien